Formal Modeling and Analysis of Timed Systems 5th International Conference, FORMATS 2007, Salzburg, Austria, October 3-5, 2007, Proceedings - Raskin, Jean-Francois.; Raskin, Jean-Francois.; Thiagarajan, P.S.; Thiagarajan, P.S. (Theoretical Computer Science and General Issues ;, 2007)
This volume consists of the proceedings of the Fifth International Conference on Formal Modelling and Analysis of Timed Systems (FORMATS 2007). The main goal of this series of conferences is to bring together diverse communities of researchers that deal with the timing aspects of computing systems. Both fundamental and practical aspects of timed systems are addressed and results reportingnewapplicationdomainsareactivelyencouraged.Further,invitedtalks that survey various aspects of this broad research domain were presented at the conference. FORMATS 2007 was co-located (during October 3–5) as a guest conference attheEmbeddedSystemsWeek,whichconstitutesaweek-longeventthatbrings togetherconferences,tutorialsandworkshopsdealingwithvariousaspectsof- bedded systemsresearchanddevelopment. Embedded Systems Week took place this year at Salzburg, Austria during September 30 - October 5, 2007. Detailed information about FORMATS 2007 can be found at http://www.ulb.ac.be/ di/formats07, while http://www.esweek.org provides an overview of the - bedded Systems Week Event. We would like to thank the organizers of the - bedded Systems Week for enabling FORMATS 2007 to be co-located at this exciting event and for providing valuable logistics support.